What are we talking about when we talk about the territorial commitment of universities? A reflection on Chilean state universities. - Labraña, Julio; Rodríguez-Ponce, Emilio; Puyol de la Fuente, Francisca (Critical Proposals in Social Work, 2023)
The purpose of this article is to propose a definition of territory for the field of higher education studies. First, it examines the uses of the concept of territory in the higher education literature and proposes an operational definition from the social systems theory, highlighting the idea of selectivity associated with the construction of territory from university organizations. Next, Chilean higher education regulations are reviewed, identifying the relevance of territory in the mission of state universities. Using the proposed definition, and in line with the literature on institutional learning, a model is introduced to analyze the relationship between state universities and territory which, considering reflection as the central axis, underlines the importance of knowledge, the distribution and interpretation of information and the development of an organizational memory. The article ends with a summary and possible lines of research in the area.